The pleasure principle vs. reality principle in Keats’ Ode to a Nightingale: A psychoanalytic perspective - Tortor, Shella Jane; Villoria, Jan Lorriene; Monteza, Ana Mae (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study examines John Keats’ Ode to a Nightingale through the lens of Sigmund Freud’s psychoanalytic theory, focusing on the interplay between the pleasure principle (the instinctive drive to satisfy basic needs and desires) and the reality principle (the governing force that directs us to fulfill needs and desires realistically). The purpose of the study is to analyze the internal conflict within the poem’s speaker, as he navigates the tension between idealized desires for transcendence and escapism (pleasure principle) and the unavoidable limitations of human mortality (reality principle). A textual analysis method is employed, applying Freud’s concepts to key passages in the poem to highlight how the speaker’s emotional struggles reflect broader psychological dynamics. By analyzing key passages, the study reveals how the speaker’s emotional turmoil illustrates broader psychological dynamics. The study connects these findings to the United Nations Sustainable Development Goal (SDG) 3, which promotes well-being and mental health, by illustrating how the poem’s exploration of inner conflict facilitates reader identification, thereby fostering self-awareness and contributing to a deeper understanding of the human condition. This research underscores the psychological depth in Ode to a Nightingale, demonstrating how literature can reflect universal struggles and contribute to a more holistic view of well-being.